Endurance estimation in hovering flight based on battery power requested on quadcopter UAV - Richard Octonius; Neno Ruseno (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2022)
In this era, Unmanned Air Vehicle (UAV) application is growing. However, there are still weaknesses in using UAVs to carry out certain missions. One of the major problems is the energy and power required to use the UAV which impacts the endurance of a UAV can hover. This study focuses on calculating the endurance and finding which configuration will produce the optimal endurance. It starts by calculating the thrust of a propeller using blade element theory which ends in calculating endurance. Using four different types of propellers, an integral formulation was devised for a constant–power battery discharge process to predict the hovering time. The result shows that APC 1238 combined with battery 6S will produce the longest endurance. The methodology is applicable for a custom quadcopter UAV.